Influential factors of KM process adoption: A social-technological based approach - Nor Shahriza, Abdul Karim; Norshidah, Mohamed; Mohamed Razi, Mohamed Jalaldeen; Lili Marziana, Abdullah (International Business School (IBS) Universiti Teknologi Malaysia (UTM), 2012)
This study seeks to investigate factors that contribute to Knowledge Management processes adoption and implementation in the Sri Lankan telecommunication industry from the socio-technical perspective. In this pursuit, this study used intention to be involved in knowledge creation and sharing based on four SECI processes construct, and identified four domains of factors that contribute to KM process adoption. These four factors are organization structure, organizational culture, IT infrastructure, and individual acceptance. A quantitative survey research approach was conducted on 313 business executives from the selected industry. The findings suggest the reasonably high level of intention to adopt KM processes among the executives surveyed. Several factors are found as significant predictors of intention to adopt KM process. These are trust & collaboration, ICT use & support, performance expectancy of KM process, and effort expectancy of KM process.